A careful and strict enquiry into the modern prevailing notions of that freedom of will, which is supposed to be essential to moral agency, virtue and vice, reward and punishment, praise and blame / by Jonathan Edwards, A.M. - Edwards, Jonathan, 1703-1758. (Tufts University. Tisch Library., 2016)
The fifth edition.; 1 online resource (xi, 5 unnumbered pages, 400, 403-415, 9 unnumbered pages, 18 pages); Final 18 pages: Remarks on the Essays on the principles of morality and natural religion, in a letter to a minister of the Church of Scotland / by Jonathan Edwards.; Text is continuous despite pagination.; Includes index.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English short titile catalogueN3251